تقييم المخاطر المهنية لعمال الغزل في اللاذقية - داؤد نسرين; شعبان رافع; محمود نيرمين (Latakia University Journal -Medical Sciences Series, 2015)
يعتبر مصنع الغزل من المصانع الأكثر خطورة بين قطاعات الصناعة بالنسبة لحدوث وتنوع المخاطر المهنية فيه, حيث يتعرض فيه العمال مباشرة لغبار القطن الذي يسبب العديد من المشاكل التنفسية , بالإضافة الى أن استخدام الآلات يسبب مشاكل كثيرة منها الرضوض والجروح, كما أن الضجيج الذي تحدثه الآلات له آثار سلبية على الأذن. وقد صنفت المخاطر المهنية وفقا" لمنظمة العمل الدولية والمنظمة العالمية للصحة المهنية إلى ست مجموعات رئيسية وهي: مخاطر بيولوجية, مخاطر فيزيائية, مخاطر كيميائية , مخاطر تلاؤمية و مخاطر نفسية. تعود أهمية إجراء هذا البحث إلى ارتفاع نسب إصابات العمل والأمراض المهنية والوفيات الناجمة عن المخاطر المهنية, ولقلة الأبحاث التي تم إجراؤها في هذا المجال في سوريا. أجريت هذه الدراسة لتحديد المخاطر المهنية التي يتعرض لها عمال الغزل باللاذقية والعوامل المتعلقة بها. أجري البحث على عينة قوامها 308عامل إنتاج في معمل الغزل باللاذقية. تم اعتماد أسلوب منهج البحث الوصفي, وقد تم استخدام الاستبيان كوسيلة لجمع البيانات من خلال إجراء مقابلات شخصية مع أفراد العينة. احتلت المخاطر الفيزيائية المرتبة الأولى بين أكثر أنواع المخاطر المهنية انتشارا" بين العمال, وكان لعدم توفر وسائل الوقاية الشخصية وعدم استخدامها من قبل العمال علاقة بزيادة حدوث هذه المخاطر, بينما لم تظهر النتائج أي علاقة ذات دلالة إحصائية بين حدوث المخاطر المهنية وبين البيانات الديموغرافية للعمال كالعمر, الخبرة والمستوى التعليمي. تقترح نتائج هذه الدراسة وضع سياسات معينة لإجراء تفتيش دوري على أماكن العمل من قبل مسؤول السلامة المهنية للتأكد من توفر ظروف العمل الآمنة للعمال وتوفر وسائل الوقاية The spinning mill factories most dangerous among industry sectors for the occurrence and diversity of occupational hazards which, where the workers exposed directly to cotton dust which causes many respiratory problems. In addition to using the machines cause many problems such as bruising and wounds, also the noise of the machines have negative effects on the ear. Occupational hazards are classified according to the International Labor Organization and the World Health Occupational Organization to six main groups biological hazards, chemical hazards ,physical hazards, ergonomic hazards and psychological hazards. The importance of this research return to the high rates of accidents at work and occupational illnesses and deaths from occupational hazards, and lack of research conducted in this area in Syria. The aim of the present study was to identify occupational hazards for textile workers in Lattakia and the related factors. The study was conducted at the spinning factory in Lattakia, a convent sample of 308 production workers. Is a descriptive research methodology, the questionnaire has been used as a means of collecting data through personal interviews with respondents. Physical hazards took first place among the most common types of occupational hazards among workers, and was the lack of personal protective equipment and and not used by the workers linked to the increased incidence of occupational hazards, while the results did not show any relationship of statistical significance between the occurrence of occupational hazards and demographic data to workers such as age, experience and education level. Our present study results advice to conduct regular inspections to workplaces by the occupational safety officer to ensure safe working conditions for workers and provide a means of personal protection and psychological support for them.